From electoral to corporate board quotas: the case of Portugal - Espírito-Santo, A. (Transforming gender citizenship: the irresistible rise of gender quotas in Europe, 2018)
In Portugal, a so-called Parity Law was approved in August 2006. According to that law, all lists presented for local, legislative, and European elections must guarantee a minimum representation of 33.3 per cent for each sex. Parties that do not respect this minimum are fined. The approval of that law places Portugal within a global trend for the adoption of such measures. This trend has intensified greatly over the last 15 years, and at the moment, more than one hundred countries have gender quotas for political office (Franceschet, Krook, and Piscopo 2012, 3). Although political gender quotas are the oldest and by far the most common ones, two further generations (Holli 2011) or groups (Meier 2013) of gender quotas have recently appeared in several countries: gender quotas for advisory boards and for boards of publicly listed and state-owned companies. Up until very recently, these two additional types of quotas were not present in Portugal, and quotas were synonymous with electoral gender quotas. However, in August 2017, a law aiming to achieve a more equilibrated representation of women and men in the administrative and fiscal organs of listed and state-owned companies was adopted.